Economic Approaches to the Technological Processes of the Plasma Work with Metals - Tamaryan, Grigor (Bulletin of Yerevan University G: Economics, 2013)
The article demonstrates the economic analysis of the plasma work with metals as the important technological approach which is actual as part of the industrial development in the metallurgy. The author analyses the economical approaches and technological steps of working with metals by use of plasma, including technical procedures and economic considerations.